Corticotectal Projections From the Premotor or Primary Motor Cortex After Cortical Lesion or Parkinsonian Symptoms in Adult Macaque Monkeys: A Pilot Tracing Study - Fregosi, Michela; Contestabile, Alessandro; Badoud, Simon; Borgognon, Simon; Cottet, Jérôme; Brunet, Jean-François; Bloch, Jocelyne; Schwab, Martin E.; Rouiller, Eric M. (Frontiers in Neuroanatomy, 2019)
The corticotectal projections, together with the corticobulbar (corticoreticular) projections, work in parallel with the corticospinal tract to influence motoneurons in the spinal cord both directly and indirectly via the brainstem descending pathways. The tectospinal tract originates in the deep layers of the superior colliculus. In the present study we analysed the corticotectal projections from two motor cortical areas, namely the premotor cortex (PM) and the primary motor cortex (M1) in eight macaque monkeys subjected to either a cortical lesion of the hand area in M1 (n=4) or Parkinson’s disease-like symptoms PD (n=4). A subgroup of monkeys with cortical lesion was subjected to anti-Nogo-A antibody treatment whereas all PD monkeys were transplanted with Autologous Neural Cell Ecosystems (ANCE). The anterograde tracer BDA was used to label the axonal boutons both en passant and terminaux in the ipsilateral superior colliculus. Individual axonal boutons were charted in the different layers of the superior colliculus. In intact animals, we previously observed that corticotectal projections were denser when originating from PM than from M1. In the present M1 lesioned monkeys, as compared to intact ones the corticotectal projection originating from PM was decreased when treated with anti-Nogo-A antibody but not in untreated monkeys. In PD-like symptoms’ monkeys, on the other hand, there was no consistent change affecting the corticotectal projection as compared to intact monkeys. The present pilot study overall suggests that the corticotectal projection is less affected by M1 lesion or PD symptoms than the corticoreticular projection previously reported in the same animals.